THE USING OF ANIMATION MOVIES MEDIA IN IMPROVING THE STUDENTS’ WRITING SKILL AT THE TENTH GRADE OF SMA NEGERI 4 PEMATANGSIANTAR - Mardin Silalahi; Yusri Puspita Sari (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2021)
The purpose of this research was to find out the effect of Using Animation Movies in Improving the Students’ Writing Skill at the Tenth Grade of SMA N 4 Pematangsiantar. This research was conducted with quantitative content analysis method. The sample of this research were 71 students that get from tenth grade especially in social class with using two class where 35 students from the control class and 36 students from experimental class which the populations were 105 students. The data of this research is the writing test students’ writing skill of narrative text that collect with pre-test and post-test. Then the result of this research wasthe score of pre-test and post-test experimental class that give an animation movies media is higher from control class where the pretest control score < 1970 (pretest of experimental) and posttest control 2118 <2380 (posttest of experimental) with the hypothesis,tcount (6.407) >ttable (1.994) at the significance level α=0,05 with the degress of freedom (df) = 34. So, Ho is rejected and Ha is accepted. It could b e conducted that the using of Animation Movies Media effect Significantly in improving the students’ Writing Skill at the tenth grade of SMA Negeri 4 Pematangsiantar